Synthesis of L-cyclic tetrapeptides by backbone amide activation CyClick strategy. (5th November 2022) - Wills, Rachel; Adebomi, Victor; Spancake, Caroline; Cohen, Ryan D.; Raj, Monika
Abstract: Cyclic tetrapeptides exhibit high cellular permeability and a wide range of biological properties and thus have gained great interest in the field of medicinal chemistry. We synthesized highly strained 12-membered head to tail cyclic peptides with varying reactive amino acids, without oligomerization using the exclusively intramolecular CyClick chemistry. This occurs by a two-step process involving the low-energy formation of a 15 atom-containing cyclic imine, followed by a chemoselective ring contraction of the peptide backbone generating a highly strained 12 atom-containing cyclic tetrapeptide. This reaction exhibited high substrate scope and generated head to tail cyclic tetrapeptides with varying amino acids at the N-terminus, showing chemoselectivity without the need for side group protection. Graphical abstract: Image 1